PENGARUH KINERJA KEUANGAN DAN MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR SEKTOR BARANG KONSUMSI TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Ela Widasari; Sumartono Sumartono (The Asia Pacific Journal Of Management Studies, 2021)
This study is to examine the effect of Financial Performance and Good Corporate Governance Mechanisms on Earnings Management in Manufacturing Companies in the Consumer Merchandise Sector Listed on the Indonesia Stock Exchange (IDX) in 2015-2019. Using secondary data with a sampling technique using purposive sampling as many as 11 companies from 52 company populations over a period of 5 years. Statistical testing using the SPSS version 22 application.The results of the partial test yielded that Return on Assets (ROA) had a negative and insignificant effect on earnings management, the Board of Commissioners had a negative and insignificant effect on earnings management. Institutional Ownership had a positive and insignificant effect on earnings management. Managerial Ownership has a positive and significant effect on earnings management. The Audit Committee has a positive and insignificant effect on earnings management. Simultaneously Return On Assets (ROA), Board of Commissioners, Institutional Ownership, Managerial Ownership and Audit Committee have a simultaneous effect on earnings management.